Parasite Fauna of Ostriches, Emus and Rheas - Nemejc Karel; Lukesova Daniela (Agricultura Tropica et Subtropica, 2012)
In most parts of the world ratite farming (i.e. farming of ostriches, emus and rheas) is a new fi eld of livestock production. These birds are livestock with broad utilisation of their products. Both wild and captive ostriches, emus and rheas may be infested with their own specifi c parasites as well as with external and internal parasites of other birds and animals. Eimeria spp. (protozoa), Houttuynia struthionis (cestoda) and Libyostrongylus douglassii (nematoda) belong to parasites causing the most serious economic losses in ratites in the world. As farming of these big birds is still in the beginning, many years of research and development are necessary to reach levels of medical and technological progress that is nowadays practised in poultry industry.